Liquid Crystals : Fundamentals - Singh, Shri (World Scientific Publishing Company, 2002)
This book introduces the basic theory and properties of liquid crystals, explaining their phases, molecular structures, and electro-optical behavior, with applications in displays, sensors, and advanced materials.